ESTIMATES OF LENGTH-BASED POPULATION PARAMETERS OF SKIPJACK TUNA (KATSUWONUS PELAMIS, LINNAEUS 1798) FROM A POLE & LINE FISHERY IN MAUMERE-SIKKA, INDONESIA - Agus Setiyawan; Michael A Rice; Fayakun Satria; Agustinus Anung Widodo (Indonesian Fisheries Research Journal, 2021)
Several population parameters of skipjack tuna (Katsuwonus pelamis) taken by pole and line gear from Maumere Waters from March 2017 to February 2018 were analyzed. A total of 2,194 skipjack tuna was sampled randomly. Fishing activities were carried out around FADs (Fish Aggregating Devices) and free fish shoal. Observers and enumerators collected data from several landing sites and by direct on-board observations. This study aims to provide length-frequency distribution by season, estimate growth mortality parameters, and estimate stock exploitation rate using FISAT software. The results showed that the total catch was dominated by skipjack tuna; up to 80% with the CPUE of 30.8 kg/person/trip, and the skipjack tuna’s length distribution ranged from 26 to 69 cm FL. Length at first capture (Lc) was 34.71 cm FL, and immature fish dominated the total catch with 53%, indicating growth overfishing. The calculated von Bertalanffy growth (VBG) parameters were L= 70.35 cm, K = 0.55 yr-1, and t0 = -0.39 yr. Natural mortality (M) was estimated to be 0.92 and fishing mortality (F) was 0.91. The mean longevity of skipjack tuna is estimated to be 3.2 years, with an exploitation rate (E) of 0.50. Sustainable exploitation of skipjack tuna determined from this analysis could be developed with an Emax of 0.73. There is a focus on reducing the catch of immature fish through various methods that include changing the fishing target area from FADs to fishing on natural fish schools and using gear modifications such as larger-sized (lower number) hooks.